Characterization of the sunflower oil-based oleogel developed by the ferulic acid/monoglyceride mixture and its application in chocolate preparation - Sheng Zhang; Sheng Geng; Hanjun Ma; Benguo Liu (Food Chemistry: X)
The ferulic acid (FA) / monoglyceride (MG) mixture could act as a gelator to structure sunflower oil at the gelator concentration (c) ≥ 4 % and the FA/MG ratios (r) of 0:100, 25:75, 50:50 and 75:25. The rectangular FA and needle-shaped MG crystals in the oleogel interlock with each other to form a 3D network, restricting the flow of oil. The gel strength and rheological performance of the oleogel were positively correlated with c and negatively correlated with storage temperature (t). Its gelation temperature was determined by c and r. Its β-carotene protective ability against ultraviolet irradiation was proportional to the FA concentration. The oleogel with r = 25:75, c = 5 % and t = 4 °C could partially substitute cocoa butter for chocolate production. With the increasing substitution rate (WCBS), the appearance, texture properties and enthalpy change of chocolate gradually deteriorated. But when WCBS ≤ 40 %, the oleogel had no significant effect on the sensory characteristics.